MP09: Canadian Community Utilization of Stroke Prevention Pilot Study-Emergency Department (C-CUSP ED). (15th May 2017) - Parkash, R.; Magee, K.; McMullen, M.; Clory, M.B.; D'Astous, M.; Robichaud, M.; Andolfatto, G.; Read, B.; Wang, J.; Thabane, L.; Atzema, C.L.; Dorian, P.; et al.
Abstract : Introduction: Atrial fibrillation (AF) is the most common sustained arrhythmia affecting 1-2% of the population. Oral anticoagulation (OAC) reduces stroke risk by 60-80% in AF patients, but only 50% of indicated patients receive OAC. Many patients present to the ED with AF due to arrhythmia symptoms, however; lack of OAC prescription in the ED has been identified as a significant gap in the care of AF patients.Methods: This was a multi-center, pragmatic, three-phase before-after study, in three Canadian sites. Patients who presented to the ED with electrocardiographically (ECG) documented, nonvalvular AF and were discharged home were included. Phase 1 was a retrospective chart review to determine OAC prescription of AF patients in each ED; Phase 2 was a low-intensity knowledge translation intervention where a simple OAC-prescription tool for ED physicians with subsequent short-term OAC prescription was used, as well as an AF patient education package and a letter to family physicians; phase 3 incorporated Phase 2 interventions, but added immediate follow-up in a community AF clinic. Theprimary outcome of the study was the rate of new OAC prescriptions at ED discharge in AF patients who were OAC eligible and were not on OAC at presentation.Results: A total of 632 patients were included from June, 2015-November, 2016. ED census ranged from 30000-68000 annual visits. Mean age was 71±15, 67±12, 67±13 years, respectively. 47.5% were women, most responsible ED diagnosis was AF in 75.8%. The mean CHA2 DS2 -VASc score was 2.6±1.8, with no difference amongst groups. There were 266 patients eligible for OAC and were not on this at presentation. In this group, the prescription of new OAC was 15.8% in Phase 1 as compared to 54% and 47%, in Phases 2 and 3, respectively. After adjustment for center, components of the CHA2 DS2 -VASc score, prior risk of bleeding and most responsible ED diagnosis, the odds ratio for new OAC prescription was 8.0 (95%CI (3.5, 18.3) p<0.001) for Phase 3 vs 1, and 10.0 (95%CI (4.4, 22.9) p<0.001), for Phase 2 vs 1). No difference in OAC prescription was seen between Phases 2 and 3.Conclusion: Use of a simple OAC-prescription tool was associated with an increase in new OAC prescription in the ED for eligible patients with AF. Further testing in a rigorous study design to assess the effect of this practice on stroke prevention in the AF patients who present to the ED is indicated.